CCN3: lactational bone booster - Nathan Xu; Kyle Yang; Mengjie Wang (Cell & Bioscience)
Abstract Mammalian reproduction requires that nursing mothers transfer large amounts of calcium to their offspring through milk. Meeting this demand requires the activation of a brain-breast-bone circuit during lactation that coordinates changes in systemic hormones, dietary calcium intake, skeletal turnover, and calcium transport into milk. Classically, increased bone resorption via increased parathyroid hormone-related protein and low estrogen levels is the main source of calcium for milk production during lactation. Over the past few decades, investigators have described many aspects of this brain-breast-bone axis during lactation, yet many unanswered questions remain. Using a comprehensive set of parabiosis coupled with in vivo µCT, bone transplant studies, cell culturing and differentiation assays, mouse genetic models, pharmacologic interventions, hepatic viral transduction, and sequencing analysis, a recent study discovered that cellular communication network factor 3 (CCN3), derived from ARHERα/Kiss1 neurons, functions as an osteogenic hormone to sustain bone formation and progeny survival during lactation. Compelling evidence has been presented to show that (1) CCN3 expression in ARHERα/Kiss1 neurons fluctuates, almost exclusively appearing during lactation; (2) CCN3 stimulates mouse and human skeletal stem cell activity, increases bone remodeling and fracture repair in young and old mice of both sexes; (3) knockdown Ccn3 transcripts in the ARHKiss1 neurons in lactating dams causes devastating bone loss and failure to sustain progeny survival. These findings suggested that the stage-specific expression of CCN3 in female ARHERα/Kiss1 neurons during lactation is a newly identified brain-bone axis evolved to sustain the skeleton in mammalian mothers and offspring.